Measuring the contents of tea lipids and comparison of qualitative analyzing methods - CHEN Yunyang; ZHAO Hangye; ZHANG Chengming; WANG Zhuoyi; CUI Yan; CAI Meisheng; ZHANG Qingbi; HU Jinxiang; HE Puming; TU Youying (浙江大学学报. 农业与生命科学版)
In order to measure the tea lipid contents in different types of tea and to analyze the tea lipid compositions, twenty tea samples such as Xihulongjing, Jiuquhongmei, Baihaoyinzhen, etc., were used as materials to analyze the lipid contents through acid hydrolysis method and Soxhlet extraction method. The results showed that the tea lipid contents tested with Soxhlet extraction method were lower than the tea lipid contents tested with acid hydrolysis method. As for the tea lipid contents, they were changed due to tea materials and processing technologies. The tea lipid contents roughly showed as follows: green tea (non-fermented tea)＞yellow tea (lightly fermented tea)＞oolong tea (semi-fermented tea)＞black tea (completely fermented tea)＞white tea (lightly fermented tea)＞dark tea (post-fermented tea). Further study on the lipid content of white tea was analyzed, and it was found that the tea lipid content of Shoumei was higher than that of Baihaoyinzhen or Bai peony, and with the increase of storage years, the tea lipid content in white tea decreased; tea lipids were composed of phospholipids, lipoproteins and free fatty acids according to the qualitative analysis results. This study provides a theoretical and practical basis for the determination of tea lipids.